Evaluate the Distribution of Heavy Elements that Dissolved in Ground Water Using IDW in AL-Wafa City, Al-Ramadi,Iraq - Rasheed, Hala A; Shaban, Auday H. (Iraqi Journal of Physics, 2021)
Groundwater can be assessed by studying water wells. This study was conducted in Al-Wafa District, Anbar Governorate, Iraq. The water samples were collected from 24 different wells in the study area, in January 2021. A laboratory examination of the samples was conducted. Geographical information systems technique was relied on to determine the values of polluting elements in the wells. The chemical elements that were measured were [cadmium, lead, cobalt and chromium]. The output of this research were planned to be spatial maps that show the distribution of the elements with respect to their concentrations. The results show a variation in the heavy elements concentrations at the studied area groundwater. The samples show different values of concentrations; for Cadmium (0.218-1.624) ppm, Lead (0.217-1.157) ppm, Cobalt (0.014-0156) ppm, and for Chromium (0.045-0263) ppm. The distribution of the materials concentrations differs for each element which is refer to the sources of pollution are not relate to industry, but it could be relate to fertilization.